Modelling characteristics of the urban form to support water systems planning. (June 2018) - Bach, Peter M.; Deletic, Ana; Urich, Christian; McCarthy, David T.
Abstract: A spatial model is presented, based on urban planning concepts for abstracting urban form characteristics in new and existing areas. Requiring input maps of land use, elevation, population and parameters from planning regulations, the model conceptualises (on a spatial grid) attributes including impervious fraction, allotment geometry and roof areas among other relevant characteristics for integrated urban water management. The model is calibrated to three different Melbourne districts, varying in size (10–60 km 2 ) and land use. Performance was evaluated by comparing modelled outputs with observations of total dwelling count, employment and spatial distribution of impervious fraction and residential roof areas. Results not only highlight reasonably good prediction, particularly with spatially variable indicators such as imperviousness across all case studies, but also logical contrasts and consistency in the chosen planning parameters across the different case study districts. Discrepancies highlight aspects needing improvement and potential for exploring auto-calibration and model sensitivity. Highlights: We present a model based on planning regulations to recreate urban form characteristics. We calibrate the model to three case studies, each using a different source of calibration data. Model performs reasonably well in reproducing total impervious fractions and roof areas. Model enables investigation of the links between urban planning and water management.